Kewajiban Nafkah Hadanah Dan Rada'ah Terhadap Anak Di Indonesia - Iman Jauhari (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
Effect of busy parents often neglected duty towards their children. So in this paper a problem concerning maintenance obligations hadanah and rada'ah for children. The method used is the approach to library research with content analysis of the various references relevant to the subject matter covered. Parents are obliged to provide a living hadanah against children because a child needs someone who can nurture, guide and educate well. Obligations of parents towards children has been started from the time the fetus until the baby where the mother is obliged to provide a living rada'ah (feeding the baby) in addition to the health of the baby also for the health of the mother. In Islam keeping the kemaslahatan and survival of a child is a parental responsibility, which should not be ignored either by the mother or father.